Water quality and prevalence of extended spectrum beta lactamase producing escherichia coli (ESBL E. coli) in Sungai Terengganu, Malaysia - Noor Haza Fazlin Hashim,; Muhammad Azroie Mohamed Yusoff,; Rachel Trevor Gunggang,; Roslina Abdul Razak,; Muhamad Zulfatihi Jaafar,; Nasehir Khan E.M. Yahaya, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Antimicrobial resistance (AMR) is a significant global issue impacting human, animal, and environmental health, as well as economic security. Water bodies, especially, are now recognized for their role in the spread of antimicrobial-resistant pathogens, though standardized monitoring methods are lacking. This study investigates the presence of extended-spectrum beta-lactamase (ESBL) producing Escherichia coli in the Sungai Terengganu River in Malaysia, focusing on water quality and ESBL E. coli monitoring. Sampling was conducted twice in 2023 at 13 locations along the river. Overall, the water quality index (WQI) classified the river as Class II (WQI = 81), with upstream regions rated as Class I, indicating minimal anthropogenic impact. Higher Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solids (TSS) in downstream areas suggested organic pollution from anthropogenic activities. Four metal elements exceeded the National Water Quality Standards (NWQS): Al (0.88 mg/L), Fe (3.45 mg/L), Cu (0.102 mg/L), and Hg (2.525 mg/L). No Pb, Cr, Se, Sn, or As were detected. Statistical analysis showed better water quality correlates with lower microbial contamination. ESBL E. coli was found in 8 of 13 sampling sites (61.5%), with the highest concentration at 800 CFU/100 mL. From 40 presumptive ESBL isolates tested, 87.5% (35 isolates) were positive for ESBL and carried additional drug resistance genes, including mcr-1, tetW, sul-1, and sul-2. These findings indicate a concerning presence of multidrug-resistant E. coli in the river, representing a potential public health risk.